Effect of silicon nanowire etching on signal‐to‐noise ratio of SiNW FETs for (bio)sensor applications. Issue 13 (1st June 2013) - Moh, T.S.Y.; Nie, M.; Pandraud, G.; de Smet, L.C.P.M.; Sudhölter, E.J.R.; Huang, Q‐A.; Sarro, P.M.
Abstract : A high signal‐to‐noise ratio (SNR) in silicon nanowire (SiNW) field effect transistors (FETs) is crucial for detecting low concentrations of biological material as the signal changes are often small and difficult to be differentiated from the baseline signal. This reported work studies the low‐frequency noise (1/ f ) as in Hooge's constant, α H, and the device detection limit of the SiNW FETs to evaluate the influence of the etching process used to define the nanowires (NWs). Two etching methods are compared: plane‐dependent etching using potassium borate in water and reactive ion etching in Cl‐based chemistry. All investigated devices have similar dopant type, doping concentration and dimensions, and were fabricated with the same process flow with the exception of the NW definition. The extracted average Hooge's constant for wet etching is found to be at least an order of magnitude lower ( α H, avg = 7.96 × 10 −4 ) compared with dry plasma‐etched devices ( α H, avg = 4.1 × 10 −2 ), indicating a lower surface roughness and/or a lower amount of surface defects. This study shows that the newly developed method improves the electrical properties of the device, making it an interesting alternative to standard approaches used for fabrication of SiNW FETs as (bio)sensors.